Evolution strategies for collaborative governance of marine microplastic pollution from the industry-research integration perspective - Li, Ruifa; Dong, Yichong; Zhao, Qi; Zheng, Mingxing; Lu, Xingyu (Frontiers in Marine Science, 2024)
Introduction Marine microplastics, are widely distributed in the global marine environment, posing a challenging issue that requires the joint efforts of global stakeholders. Methods To effectively address the issue of marine microplastic pollution (MMP) governance and analyze the dynamic changes in governance willingness of various participants under different scenarios, this paper meticulously constructs a game theory framework encompassing polluting enterprises, research institutions, and environmental organizations. Results (1) On the political level, the implementation of continuous and strong economic penalty mechanisms is an effective means to deter enterprises from evading MMP governance responsibilities. However, the effective execution of this strategy highly depends on the participation and supervision of environmental organizations. Therefore, it is essential to assign more roles and responsibilities to environmental organizations to ensure the thorough execution of governance measures. (2) On the technical level, the effectiveness of research directly determines the functional status of enterprises and research institutions in the MMP governance decision-making system. Weaker entities tend to make decisions following the behavioral preferences of dominant entities. Thus, deepening the integration of industry and research and fully unleashing the effectiveness of research outcomes in MMP governance is a key path to enhancing overall governance efficiency and effectiveness. (3) On the economic level, high governance costs often become a significant factor limiting the enthusiasm of all parties to participate. However, when innovative cooperation models achieve cost sharing and benefit sharing, the governance willingness of participants significantly increases. It is evident that optimizing resource allocation, improving the efficiency of fund utilization, and establishing a diversified and sustainable funding guarantee mechanism are crucial for advancing the in-depth progress of MMP governance. Discussion In summary, this study not only provides profound theoretical insights into the interaction relationships and behavioral choices of multiple stakeholders in MMP governance but also offers practical strategic recommendations for constructing an efficient and collaborative governance system.